MATHEMATICAL MODELS OF CREATION OF A SUBSYSTEM OF ENSURING SAFETY OF INFORMATION IN THE DISTRIBUTED INFORMATION SYSTEMS - D. O. Esikov; R. N. Akinshin; P. I. Abramov; L. E. Loutina (Научный вестник МГТУ ГА)
Practical implementation of the concept of a distributed information system requires the implementation of a complex scientific-technical problems related to the choice of composition and use of storage and processing of information, creation and use of common data arrays, information security, etc. Fundamentally, a modern distributed information system is a system of communication and information transmission as well as a storage and data processing system. Storage and data processing system is designed for organization of reliable and fault-tolerant data storage, high-performance servers to access storage devices and information processing. The measure of quality, and in some cases indicator of functioning of data storage and processing system is proposed. The tasks that need to be tackled when constructing and operating the storage and processing requirements of highly reliable data storage, as well as their following configurations: determination of the number and location of centers of data storage and processing in distributed information systems; choice of the composition of the complex used for storage in the storage centers and data processing, with the organization of a backup subsystem, the backup and restore data. The task of storage structure optimization according to the criterion of maximum values of the readiness factor of the storage system is formed. This problem is reduced to the kind of problems of integer linear programming with Boolean variables, this fact allows to apply the existing methods for its solvation. A method for determining the rational level of expenditure on the formation of the complex used for storage in the storage and data processing system based on the use of elements of probability theory and the theory of well-being (the principle of Pareto optimality) is developed. The optimal solution of the problem by optimizing a linear convolution is obtained.